1973
DOI: 10.1016/0020-7225(73)90004-9
|View full text |Cite
|
Sign up to set email alerts
|

Two bonded half planes with a crack going through the interface

Abstract: Type of Report and Period CoveredContractor Report 14. Sponsoring Agency Code Supplementary Notes AbstractThe plane problem of two bonded elastic half planes containing a finite crack perpendicular to and going through the interface is considered. The problem is formulated as a system of singular integral equations with generalized Cauchy kernels. Even though the system has three irregular points, it is shown that the unknown functions are algebraically related at the irregular point on the interface and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 243 publications
(82 citation statements)
references
References 14 publications
2
80
0
Order By: Relevance
“…-7-Singular behavior of the solution of integral equations having similar generalized Cauchy kernels was studied in detail in [1] and [2]. Following the complex function technique outlined in [6] and using the procedure described in [1] and [2], if we define the unknown functions f-j and f« in terms of unknown bounded functions g-j and g 2 and unknown powers a-| , 3-j .…”
Section: The Integral Equations For the General Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…-7-Singular behavior of the solution of integral equations having similar generalized Cauchy kernels was studied in detail in [1] and [2]. Following the complex function technique outlined in [6] and using the procedure described in [1] and [2], if we define the unknown functions f-j and f« in terms of unknown bounded functions g-j and g 2 and unknown powers a-| , 3-j .…”
Section: The Integral Equations For the General Problemmentioning
confidence: 99%
“…In studying the fracture of composite materials which consist of more than one perfectly bonded homogeneous elastic phase with different mechanical properties, it was shown that the singular behavior of the stress state in the close neighborhood of a crack tip does not remain "self-simi1ar" as it enters and crosses an interface separating two phases of the composite [1,2]. If the crack tip remains in the same homogeneous medium as it propagates, during the crack propagation the characteristic *This work was supported by the National Aeronautics and Space Administration under the Grant NGR-39-007-011 and by The National Science Foundation under the Grant GK 11977.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cook and Erdogan (1972) used the Mellin transform method to derive the governing equation of finite cracks perpendicular to an interface and obtained the stress intensity factors. Erdogan and Biricikoglu (1973) solved the problem of two International Journal of Solids and Structures 40 (2003) www.elsevier.com/locate/ijsolstr bounded half planes with a crack going through the interface. Bogy (1971) investigated the stress singularity of an infinite crack terminated at the interface with an arbitrary angle.…”
Section: Introductionmentioning
confidence: 99%
“…Description of such techniques also falls outside the scope of this article. Among thesê a one may mention the methods usedto evaluate such physical quantities as the stress intensity factors, the strain energy release rate, and the crack 91 opening displacement directly in terms of the (calculated) density functions of the integral equations (see, for example, [28] , [29] , [311- [34]). …”
Section: The Fundamental Functions Mmentioning
confidence: 99%